2017
DOI: 10.1111/jch.13139
|View full text |Cite
|
Sign up to set email alerts
|

Independent predictors of effective blood pressure control in patients with hypertension on drug treatment in Brazil

Abstract: Population assessment of effective blood pressure (BP) control is fundamental for reducing the global burden of hypertension, especially in low-and middle-income countries. The authors evaluated the effectiveness of BP control and determined independent predictors associated with effective control among patients with hypertension on drug treatment in a large cross-sectional study performed in two metropolitan areas in Brazil's southeast region. A total of 43 647 patients taking antihypertensive treatment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It has been observed that patients who are aware that elevated BP levels can lead to a reduction in life expectancy are more compliant with their hypertensive medications and follow-up visits [28]. Evidence shows that knowledge about SBP has been identified as one of the independent predictors of blood pressure control [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that patients who are aware that elevated BP levels can lead to a reduction in life expectancy are more compliant with their hypertensive medications and follow-up visits [28]. Evidence shows that knowledge about SBP has been identified as one of the independent predictors of blood pressure control [29].…”
Section: Discussionmentioning
confidence: 99%
“…We then applied multivariate binary logistic regression to estimate the relationships between multiple independent variables and poorly controlled aH and T2D. Variables with p-values < 0.05 in univariate analyses were considered for the multivariable model, but the final selection of variables was guided by previous studies [12][13][14][15][16][17] and expert knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…While prior findings demonstrate varying control rates across diverse healthcare settings, the factors contributing to these disparities are intricate and multifaceted. earlier research has illuminated several factors that contribute to poor aH and T2D control, including advanced age, socio-economic disparities, gender differences, extended disease duration, obesity, unhealthy lifestyle habits, difficulties with treatment adherence, disparity between knowledge and actions and mental health issues [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…High BMI and a family history of hypertension were risk factors for hypertension control, similar to previous results. Costa Filho et al [ 30 ] showed that obesity is an independent predictor of BP control in Brazilian hypertensive patients. BMI is a measure of obesity that can be improved by exercise and diet.…”
Section: Discussionmentioning
confidence: 99%